1999 год. Весенняя сессия, 18 июня - 16 авг. - Теплова М. О. (2002)
Экземпляры: КХ (20060503) / Инвентарный номер: 1056453 / Цена: 20.00 / Сис.шифр: 67.400 / Авт.знак: Г 72 / ГРНТИ: 10 / ББК: 67.400.621